The Impact of the Picture and Picture Learning Model on Student Activity and Social Studies Outcomes (A Case Study of 4th Grade Students in Gowa District) - Basmala Basmala; Kaharuddin Kaharuddin; Suardi Suardi (Universitas Cokroaminoto Palopo, 2024)
This study examines the impact of the Picture and Picture learning model on student engagement and academic performance in Social Studies among Grade IV students at SD Inpres Paccinongan, Gowa Regency. Low student engagement in the learning process and suboptimal academic performance are key issues faced in primary education. This study used a quasi-experimental design with a Nonequivalent Control Group methodology. The study population consisted of Grade IV students from two classes, with a total sample of 48 students selected using random sampling techniques. Data were collected through observations and tests, then analyzed using descriptive and inferential statistical techniques. The results indicated that the Picture and Picture learning model had a significant positive effect on student engagement and academic performance. The significance values for student activity (p = 0.040) and learning outcomes (p = 0.016) were both below the standard alpha level of 0.05, indicating the effectiveness of this model in enhancing student engagement and their academic results. These findings provide evidence that the application of a visual-based learning model, such as Picture and Picture, can be an effective solution to address low student engagement and learning outcomes in Social Studies education at the primary school level. The adoption of this learning paradigm is recommended to be expanded in Social Studies education at primary schools to improve the overall quality of education and academic performance of students.